the Pembentukan Karakter Peduli Lingkungan melalui Pendidikan Agama Islam di Sekolah Dasar - Ica Cahayaningsih; Khozin K; Moh. Kamal (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2022)
This research is motivated by environmental problems which are mostly caused by human activities. Human awareness needs to be built through the formation of environmental care characters in schools that are integrated into subjects, including Islamic Religious Education (PAI) subjects, in order to maintain and utilize natural resources wisely and responsibly. This study aims to determine how the formation of environmental care character through PAI in SD Muhammadiyah 4 Batu. This research uses a qualitative approach and is also a case study research. Data collection techniques were carried out by interview, observation and documentation. Data analysis is done by collecting data, presenting data, condensing data, and drawing conclusions/verification. To obtain the validity of the data, this study used the source triangulation method. The results of this study indicate that the formation of a caring character for the environment through PAI in SD Muhammadiyah 4 Batu is carried out through three components, namely school policy programs and an environmentally friendly curriculum, which are described in the vision and mission of a school with an environmental culture and curriculum development with a monolithic or integrated model; perpetrators of character building caring for the environment which in this case are PAI teachers and parents; updating the facilities and infrastructure used to support learning.